Understanding of cardiovascular disease risk factors among Bangladeshi immigrants in New York City. Issue 4 (19th May 2019) - Patel, Mihir; Boutin-Foster, Carla; Phillips, Erica
ABSTRACT: Objectives: Among all South Asians, Bangladeshis have the highest prevalence of cardiovascular disease (CVD). The purpose of our study was to compare the understanding of CVD risk factors among Bangladeshi immigrants to the general Caucasian population in the U.S. Design: We surveyed Bangladeshi immigrants in Queens, New York using a CVD risk factor knowledge instrument used in the Coronary Artery Risk Development in Young Adults (CARDIA) study to assess awareness of risk factors. Using multivariate regression modeling, we compared scores on the knowledge instrument between Bangladeshis we surveyed and Caucasians from the CARDIA study, controlling for potential confounders. We subsequently examined the frequency of mentioning each risk factor to understand what was driving the difference in the overall score. Results: The proportion of Bangladeshis scoring low on the knowledge assessment was 0.53, where as the proportion of whites scoring low in the CARDIA study was 0.32 ( p value < .001). Whites were 34% more likely to score high than Bangladeshis (adjusted odds ratio [aOR] 1.34, 95% confidence interval [CI] 1.19–1.52). Bangladeshis were more likely to mention diet and cholesterol as risk factors and less likely to mention lack of exercise, being overweight, and smoking as risk factors. Conclusion: Understanding of cardiovascular disease risk factors was lower among Bangladeshis than whites. This was driven by Bangladeshis having less awareness regarding how exercise and being overweight contribute to CVD. Community based interventions and community health partnerships should target these behavioral risk factors in the Bangladeshi population.